Properties of particleboard from rubberwood and Raintree / Mohd Haniff Ramli - Ramli, Mohd Haniff (2013)
The objective of this study to investigate the physical and mechanical properties of particleboard from rubberwood and raintree at different proportion level and properties were evaluated based on the Malaysian Standard (MS 1036: 2006). Variable factors were as resin content of UF (8, 10, and 12%) and different species. The physical and mechanical data presented here. Were analyzed using software package used for statistical analysis (SPSS) to determine significant different of the variable. From this study, increased of Thickness swelling of particleboard, for bending properties, there is no significant different for each species and resin had significant different when increase of resin content. In term of Internal Bonding strength, decrease in rubberwood proportion resulted in decreased in the Internal Bonding strength of the particleboard.